Effect of geometric and magnetic boundary conditions on magnetic islands in 3D force-free ideal MHD equilibria. (15th February 2021) - Benedett, T.E.; Hansen, C.J.
Abstract: Three-dimensional boundary features and magnetic perturbations affect the magnetic topology of the force-free ideal MHD equilibria formed within a given volume. The use of the PSI-Tet 3D finite-element equilibrium code reveals the existence of magnetic islands inside such equilibria within boundaries with three-dimensional features in configurations that directly depend on the natures of those features. The nature and limits of the influence of such features are explored, as is the influence of flux boundary conditions to qualitatively identify the structure of magnetic islands in Taylor state equilibria with three-dimensional boundary conditions.